Pengaruh Pemberian Latihan Koordinasi terhadap Peningkatan Fungsional pada Penderita Parkinson's Disease - Riani baiduri siregar; Heri saputra; Rudi Purwana; Ani Ramadani (Pusat Riset dan Inovasi Nasional, 2026)
Parkinson's disease is a chronic progressive chronic neurodegenerative disorder. In general, the clinical symptoms of this disease include the classic triads consisting of resting tremor, rigidity and akinesia or bradykinesia, which is accompanied by a decrease in postural reflex. To know there is influence of co-ordination training to increase functional ability in patient of Parkinson desease. The design of this study was experimental experimental design with pre-post test design to see the different effects of co-ordination training on the improvement of functional ability in measuring with SARA in patients with Parkinson's desease. With a sample size of 6 people for 4 weeks. With frequency 3 times per week. on the number of sample of 6 people who meet the inclusion and exclusion criteria with the result of statistic test on the pre test test score and post test obtained p value of Asymp value. Sig. (2-tailed)) = 0.404 or p <0.05. These results indicate that there is a significant effect between before and after treatment, because the value of p ≤ 0,000. This means that Ha is accepted and Ho is rejected, meaning that giving coordination training, for 4 weeks with frequency 3 times per week can significantly improve functional ability.The provision of coordination exercise was able to improve the ability of people in Parkinson's.